Technology Proficiency Development and Business Educators' Job Effectiveness in Public Universities in Rivers and Bayelsa States - Fortune Omasirichi Sam-Eleyi; Ann Boma Green Owota (Researchparks Publishing, 2026)
This study examined the relationship between technology proficiency development and Business Educators' job effectiveness in public universities. Specifically, it investigated the relationship between web searching skill acquisition, digital problem-solving skill acquisition, and job effectiveness. The study was guided by two research questions and two null hypotheses tested at a 0.05 level of significance. A correlation survey design was adopted, and the population consisted of 72 Business Educators in public universities, with a census sampling of all respondents used for the study. Data were collected using two structured questionnaires titled “Technology Proficiency Development Questionnaire (TPDQ)” and “Job Effectiveness of Business Educators Questionnaire (JEBEQ)”. The instruments were validated by experts in Business Education and showed high reliability coefficient, with Cronbach Alpha coefficients of 0.93, 0.98, 0.98 for web searching skills, digital problem-solving skills, and job effectiveness respectively, and an overall reliability of 0.96. The questionnaires were administered with the assistance of one research assistant, and all 72 copies were returned and used for analysis. Data were analysed using Pearson Product Moment Correlation to answer the research questions and test the null hypotheses. Findings revealed moderate positive relationships between web searching skills and job effectiveness, as well as between digital problem-solving skills and job effectiveness. Business Educators proficient in web searching were found to be more efficient and resourceful in their academic tasks, while those with strong digital problem-solving skills demonstrated higher productivity and adaptability in their work. The study indicates that technology proficiency development, particularly in web searching and digital problem-solving, enhances the job effectiveness of Business Educators. Based on these findings, it was recommended that Business Educators should continually improve their technology proficiency to optimise the use of digital learning facilities, and that digital learning tools and training should be incorporated into the Business Education curriculum to improve professional competence and teaching outcomes.